Enseñanza de las normas internacionales de contabilidad sector público en los programas de contaduría pública acreditados internacionalmente en Colombia (2020)
The accounting profession has had significant changes in the homogenization of international standards, and therefore accounting education has been seen as a necessity to reflect on these contexts and seek how to trigger the constant evolution in the training of future Public Accountants, so that the problems and updates in the field are applicable. Therefore, the question arises in relation to the teaching of International Public Sector Accounting Standards (IPSAS) in the process of academic training, taking into account the thematic content and methodologies taught in Universities with Internationally Accredited Accounting Programs in Colombia. This research allows us to be a tool to analyze the approach to the teaching of standards within the Public Accounting programs and constitutes a contribution to a better understanding of the current situation of the subject plans offered and to be offered, having elements of judgment in their application.